Microstructure and mechanical properties of Ti nitride/Ni metal-based composites fabricated by reactive sintering. Issue 8 (1st June 2019) - Chen, Yi-Cheng; Fan, Fang-Yu; Tsai, Meng-Hsiu; Wu, Chien-Hui; Chen, Shyi-Tien; Ou, Shih-Fu
Abstract: In this study, a Ti nitride/Ni metal-based composite was fabricated by the carbothermal reduction reaction during the sintering process. After cold isostatic pressing, green compacts consisting of 50 wt% Ti and 50 wt% Ni were soaked in a water-based hot forging lubricant followed by sintering in air at 850, 950, and 1050 °C. The effects of the sintering temperature on the wear resistance and the compressive strength of the composites were investigated. During sintering, Ti particles were transformed to Ti nitride as TiN0.3 at 850 °C, and then gradually transformed to TiN0.3 and TiN at 950 °C accompanied by TiO2 formation. The Ti oxide layer surrounding the outer surface of the Ti nitride particles has a hardness of 327.5 HV, which is lower than that of the Ti nitride particles (1224.0 HV) and higher than that of the Ni matrix (77.2 HV). The oxide layer is regarded as a buffer layer which can improve the adhesion of the Ti nitride particles and the Ni matrix. The compact sintered at 950 °C had the highest wear resistance and compressive strength among all the compacts due to its low porosity and thick oxide layer. The compact sintered at 850 °C had the lowest wear resistance, and the main fracture mechanism realizes due to the detachment of the Ti nitride particles from the Ni matrix. The wear fracture mechanism of the compact sintered at 1050 °C explained by the enlargement of the pores in the Ti nitride particle by abrasion.